Analysis of Social Business Strategy (Case Study in Rumah Harapan Kita Foundation) - Salmia Hany; Mira Nurfitriya; Nizza Nadya Rachmani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to create an overview of business strategies, identify business strategies using the social enterprise model canvas and SWOT models, and formulate appropriate business social business strategies. The object of this research is the Rumah Harapan Kita Foundation, which is one of the social businesses in Tasikmalaya City. The method used is qualitative with a case study approach. The types of data used are primary and secondary with data collection techniques using observation techniques and unstructured interviews. Primary data was obtained from an in-depth interview process with the Rumah Harapan Kita Foundation, while secondary data was obtained from documents, websites, and foundation archives. The informant for this research is the CEO and Director of Entrepreneur of Rumah Harapan Kita Foundation. Data analysis uses the model analysis method from Miles and Hubermen (1992), namely: reducing data as a form of data sorting; processing data as data presentation; and verifying the conclusions of the data that has been analyzed. The research results show that the Rumah Harapan Kita Foundation's business strategy has not been structured systematically. Then, based on the results of the analysis using SWOT and SEMC, 8 SEMC elements need to be developed. So the formulation of Rumah Harapan Kita Foundation's business strategy is focused on the elements of customer segments, value propositions, channels, customer relationships, revenue streams, key activities, key partners, and impact & measurement.